疏肝肺积方结合心理干预对原发性肺癌患者生存质量的影响 (Zhongguo Fei Ai Za Zhi, 2012)
BACKGROUND AND OBJECTIVE: Primary lung cancer is one of the most common malignant tumors. It causes great pain and mood disorders to patients, and significantly reduces their quality of life. The aim of the current study is to evaluate the effect of Feiji Decoction for soothing the liver combined with psychotherapy on quality of life (QoL) and physical status of patients with primary lung cancer. METHODS: A total of 118 patients with primary non-small cell lung cancer were randomly divided into two groups. The 57 patients in the combined therapy group were treated with Feiji Decoction for soothing the liver and psychotherapy combined with chemotherapy, whereas the 61 patients in the control group were treated with chemotherapy only. Both groups were observed for the two treatment courses. The European Organization for Research and Treatment of Cancer QoL Questionnaire LC-43 (EORTC QLQ-LC43) was used to assess the QoL of every patient in both groups before and after treatment scales. At the same time, physical status was assessed using the Karnofsky performance status (KPS) and East Cooperative Oncology Group performance status (ECOG). RESULTS: The scores of physiology function, role function, emotion function, cognize function, society function, and general health in the therapy group were higher than that of the control group. The therapy group also showed better QoL results than the contol group. Significant differences were observed between the two groups (P < 0.01). Meanwhile, the scores of fatigue, vomit, pain, polypnea, insomnia, anorexia, constipation, and specific manifestation of lung cancer in the therapy group were obviously lower than that of the control group; more patients were observed to be relieved. Significant differences between the two groups were observed (P < 0.01). The KPS and ECOG scores of the patients were observed to have improved and stabilized in the therapy group than that of the control group; the differences were statistically significant (P < 0.01). CONCLUSION: Feiji Decoction for soothing the liver combined with psychotherapy can alleviate the clinical symptoms, elevate the physical status, and improve the QOL of patients with primary lung cancer. Thus, this therapy has a good clinical therapeutic effect.